2017
DOI: 10.17116/oftalma2017133149-54
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing effect of orthokeratology lenses (ten-year follow-up results)

Abstract: Long-term wear of orthokeratology lenses is able to slow down the axial eye growth, i.e. the progression of myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 13 publications
0
7
0
3
Order By: Relevance
“…76 A study 77 indicates that toric Ortho-K can reduce corneal astigmatism by 48.1% (from 2.35 D to 1.22 D), whereas spherical Ortho-K resulted in a 10.5% decrease (2.29 D -2.05 D). In moderate-tohigh astigmatism, toric Ortho-K also gave better myopia control effect of 55.6% when compared to spherical Ortho-K. A 10-year follow-up study 78 revealed that the increase in AL was more in younger children with a high baseline myopia and that Ortho-K control stabilises after seven years, although a decelerating effect was reported in AL elongation in the early years. 78 An important feature of Ortho-K is that it can create large optical treatment effect in moderate-to-high myopia unlike other forms of optical treatment.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…76 A study 77 indicates that toric Ortho-K can reduce corneal astigmatism by 48.1% (from 2.35 D to 1.22 D), whereas spherical Ortho-K resulted in a 10.5% decrease (2.29 D -2.05 D). In moderate-tohigh astigmatism, toric Ortho-K also gave better myopia control effect of 55.6% when compared to spherical Ortho-K. A 10-year follow-up study 78 revealed that the increase in AL was more in younger children with a high baseline myopia and that Ortho-K control stabilises after seven years, although a decelerating effect was reported in AL elongation in the early years. 78 An important feature of Ortho-K is that it can create large optical treatment effect in moderate-to-high myopia unlike other forms of optical treatment.…”
Section: Discussionmentioning
confidence: 93%
“…In moderate-tohigh astigmatism, toric Ortho-K also gave better myopia control effect of 55.6% when compared to spherical Ortho-K. A 10-year follow-up study 78 revealed that the increase in AL was more in younger children with a high baseline myopia and that Ortho-K control stabilises after seven years, although a decelerating effect was reported in AL elongation in the early years. 78 An important feature of Ortho-K is that it can create large optical treatment effect in moderate-to-high myopia unlike other forms of optical treatment. Orthokeratology is also comparable to low-dose atropine in reducing myopia progression.…”
Section: Discussionmentioning
confidence: 93%
“…Известно, что миопия формируется в детском возрасте, имеет прогрессирующее течение и в Российской Федерации в структуре заболеваний глаза и его придаточного аппарата у детей уже занимает первое место, составляя 34 % [2]. В связи с этим оправдано широкое использование ортокератологии в офтальмопедиатрической практике как признанного метода стабилизация близорукости и предотвращения перехода в миопическую болезнь [3][4][5][6][7][8][9][10]. С 2013 года ортокорнеальная коррекция (ОК-коррекция) включена в Федеральные клинические рекомендации «Диагностика и лечение близорукости у детей» (Национальный протокол), утвержденные Всероссийской Ассоциацией врачей-офтальмологов [11].…”
Section: Introductionunclassified
“…Убедительно показано в эксперименте, что относительный гиперметропический периферический дефокус стимулирует осевое удлинение глаза и миопизацию рефракции, а миопический дефокус, напротив, тормозит рост глаза и усиление рефракции [1][2][3]. В клинике эти факты находят косвенное подтверждение благодаря известному тормозящему прогрессирование близорукости эффекту ортокератологии (ОК) и других оптических средств, наводящих миопический дефокус на периферию сетчатки [4][5][6].…”
unclassified